2019
DOI: 10.1007/978-3-662-58771-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Generalized Łoś-Tarski Theorem

Abstract: We present a new proof of the generalized Loś-Tarski theorem (GLT(k)) introduced in [6], over arbitrary structures. Instead of using λ-saturation as in [6], we construct just the "required saturation" directly using ascending chains of structures. We also strengthen the failure of GLT(k) in the finite shown in [7], by strengthening the failure of the Loś-Tarski theorem in this context. In particular, we prove that not just universal sentences, but for each fixed k, even Σ 0 2 sentences containing k existential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Our result also greatly strengthens a previous result by Sankaran [15] which showed that for each k there is an extension-closed property of finite structures definable in FO but not in Π 2 with k leading universal quantifiers. Indeed, our result answers (negatively) Problem 2 in [15].…”
Section: Introductionsupporting
confidence: 89%
“…Our result also greatly strengthens a previous result by Sankaran [15] which showed that for each k there is an extension-closed property of finite structures definable in FO but not in Π 2 with k leading universal quantifiers. Indeed, our result answers (negatively) Problem 2 in [15].…”
Section: Introductionsupporting
confidence: 89%
“…Acknowledgment. We thank Abhisekh Sankaran for mentioning to the first author the question of whether Tait's Theorem generalizes to graphs (see also [23]).…”
mentioning
confidence: 99%
“…Let f : N → N be a computable function. Furthermore, let w be defined by (23), where I is an interpretation for := M according to Lemma 5.6. Then there is a w ∈ {0, 1} * such that Graph( w ) is closed under induced subgraphs (and hence equivalent in the class of graphs to a universal sentence) but w is not equivalent in the class of finite graphs to a universal sentence of length less than f(| w |).…”
mentioning
confidence: 99%